Volume delivery during high frequency oscillation. Issue 2 (1st March 1998) - Dimitriou, G; Greenough, A; Kavvadia, V; Laubscher, B; Milner, A D
Abstract : AIM: To examine the delivered volume during "high volume strategy" high frequency oscillation, used as rescue treatment in preterm infants; and to identify factors, other than frequency and oscillatory amplitude, influencing the magnitude of volume delivery. METHOD: Twenty infants (median gestational age 29 weeks) were studied on 45 occasions. Two oscillator types were used (SensorMedics and SLE). Delivered volume was measured under clinical conditions with the arterial blood gases within a predetermined range. A specially calibrated pneumotachograph system was used. RESULTS: Overall, the median delivered volume was 2.4 ml/kg (range 1.0 to 3.6 ml/kg); on 32 occasions the delivered volume was greater than 2.0 ml/kg and on seven greater than 3.0 ml/kg. The delivered volume related significantly to disease severity; there was an inverse correlation between delivered volume and both the oxygenation index (OI) (r=−0.51) and AaDO2 (r=−0.54). CONCLUSION: Delivered volume during HFO may, in certain infants, exceed the anatomical dead space, permitting some direct alveolar ventilation.